Interactions of miR-34b/c and TP53 Polymorphisms on the Risk of Intracranial Aneurysm - Lijuan Li; Xiutian Sima; Peng Bai; Lushun Zhang; Hong Sun; Weibo Liang; Jianxing Liu; Lin Zhang; Linbo Gao (Clinical and Developmental Immunology)
Several lines of evidence indicate that inflammatory processes play a key role in the happening and development of intracranial aneurysm (IA). Recently, polymorphisms in the TP53 gene were shown to be associated with inflammation and inflammatory disease. The aim of this study was to investigate the interactions of miR-34b/c and TP53 Arg72-Pro polymorphisms on the risk of IA in a Chinese population. A total of 590 individuals (including 164 patients with IA and 426 controls) were involved in this study. The polymorphisms (i.e., miR-34b/c rs4938723 and TP53 Arg72-Pro) were genotyped by polymerase chain reaction-restriction fragment length polymorphism assay and DNA sequencing. We found that the CC genotype of miR-34b/c rs4938723 was significantly associated with a decreased risk of IA compared with the TT genotype. Moreover, a significant gene interaction of the carriers with the combined genotypes of miR-34b/c rs4938723CC and TP53 Arg72Pro CG/CC/GG had a decreased risk of IA, compared with those carrying miR-34b/c rs4938723CT/TT+TP53 Arg72Pro GG/CG/CC combined genotypes. These findings suggest that the miR-34b/c rs4938723CC and TP53 Arg72-Pro polymorphisms may be involved in the susceptibility to IA.